Silica, Silicosis, and Autoimmunity - Pollard, Kenneth Michael (Frontiers in Immunology, 2016)
Inhalation of dust containing crystalline silica is associated with a number of acute and chronic diseases including systemic autoimmune diseases. Evidence for the link with autoimmune disease comes from epidemiological studies linking occupational exposure to crystalline silica dust with the systemic autoimmune diseases SLE, SSc and RA. Although little is known regarding the mechanism by which silica exposure leads to systemic autoimmune disease, there is a voluminous literature on silica exposure and silicosis that may help identify immune processes that precede development of autoimmunity. The pathophysiology of silicosis consists of deposition of silica particles in the alveoli of the lung. Ingestion of these particles by macrophages initiates an inflammatory response which stimulates fibroblasts to proliferate and produce collagen. Silica particles are encased by collagen leading to fibrosis and the nodular lesions characteristic of the disease. The steps in the development of silicosis, including acute and chronic inflammation and fibrosis, have different molecular and cellular requirements suggesting that silica-induced inflammation and fibrosis may be mechanistically separate. Significantly, it is unclear whether silica-induced inflammation and fibrosis contribute similarly to the development of autoimmunity. Nonetheless, the findings from human and animal model studies are consistent with an autoimmune pathogenesis that begins with activation of the innate immune system leading to proinflammatory cytokine production, pulmonary inflammation leading to activation of adaptive immunity, breaking of tolerance, autoantibodies and tissue damage. The variable frequency of these immunological features following silica exposure suggests substantial genetic involvement and gene/environment interaction in silica-induced autoimmunity. However numerous questions remain unanswered.